ICCREM 2017. proceedings of the International Conference on Construction and Real Estate Management 2017, November 10-12 2017, Guangzhou, China - Wang, Yaowu; Pang, Yongshi; Shen, Qiping; Zhu, Yimin (College teacher) (American Society of Civil Engineers, 2017)
This collection contains 41 peer-reviewed papers on prefabricated buildings, industrialized construction, and public-private partnerships. Topics include: risk assessment and systems analysis; prefabricated buildings and construction schedules; life cycle analysis and the environmental performance of prefabricated materials; and construction supply chains.